Putative calcium-binding domains of the Caenorhabditis elegans BK channel are dispensable for intoxication and ethanol activation - Davis, S. J. (Genes Brain Behav, 2015)
Alcohol modulates the highly conserved, voltage- and calcium-activated potassium (BK) channel, which contributes to alcohol-mediated behaviors in species from worms to humans. Previous studies have shown that the calcium-sensitive domains, RCK1 and the Ca(2+) bowl, are required for ethanol activation of the mammalian BK channel in vitro. In the nematode Caenorhabditis elegans, ethanol activates the BK channel in vivo, and deletion of the worm BK channel, SLO-1, confers strong resistance to intoxication. To determine if the conserved RCK1 and calcium bowl domains were also critical for intoxication and basal BK channel-dependent behaviors in C. elegans, we generated transgenic worms that express mutated SLO-1 channels predicted to have the RCK1, Ca(2+) bowl or both domains rendered insensitive to calcium. As expected, mutating these domains inhibited basal function of SLO-1 in vivo as neck and body curvature of these mutants mimicked that of the BK null mutant. Unexpectedly, however, mutating these domains singly or together in SLO-1 had no effect on intoxication in C. elegans. Consistent with these behavioral results, we found that ethanol activated the SLO-1 channel in vitro with or without these domains. By contrast, in agreement with previous in vitro findings, C. elegans harboring a human BK channel with mutated calcium-sensing domains displayed resistance to intoxication. Thus, for the worm SLO-1 channel, the putative calcium-sensitive domains are critical for basal in vivo function but unnecessary for in vivo ethanol action.